Human Keratinocyte Response to Superantigens - Schlievert, Patrick M. (mSphere, 2020)
Staphylococcus aureus and Streptococcus pyogenes are significant human pathogens, causing infections at multiple body sites, including across the skin. Both are organisms that cause human diseases and secrete superantigens, including toxic shock syndrome toxin-1 (TSST-1), staphylococcal enterotoxins (SEs), and streptococcal pyrogenic exotoxins (SPEs). On the skin, human keratinocytes represent the first cell type to encounter these superantigens. We employed transcriptome sequencing (RNA-seq) to evaluate the human primary keratinocyte response to both TSST-1 and staphylococcal enterotoxin B (SEB) in triplicate analyses. Both superantigens caused large numbers of genes to be up- and downregulated. The genes that exhibited 2-fold differential gene expression compared to vehicle-treated cells, whether up- or downregulated, totaled 5,773 for TSST-1 and 4,320 for SEB. Of these, 4,482 were significantly upregulated by exposure of keratinocytes to TSST-1, whereas 1,291 were downregulated. For SEB, expression levels of 3,785 genes were upregulated, whereas those of 535 were downregulated. There was the expected high overlap in both upregulation (3,412 genes) and downregulation (400 genes). Significantly upregulated genes included those associated with chemokine production, with the possibility of stimulation of inflammation. We also tested an immortalized human keratinocyte line, from a different donor, for chemokine response to four superantigens. TSST-1 and SEB caused production of interleukin-8 (IL-8), MIP-3α, and IL-33. SPEA and SPEC were evaluated for stimulation of expression of IL-8 as a representative chemokine; both stimulated production of IL-8. IMPORTANCE Staphylococcus aureus and Streptococcus pyogenes are common human pathogens, causing infections that include the skin. Both pathogens produce a family of secreted toxins called superantigens, which have been shown to be important in human diseases. The first cell types encountered by superantigens on skin are keratinocytes. Our studies demonstrated, that the human keratinocyte pathway, among other pathways, responds to superantigens with production of chemokines, setting off inflammation. This inflammatory response may be harmful, facilitating opening of the skin barrier.